An Analysis of Significant Contributions to the International Business Literature - Morrison, Allen J.; Inkpen, Andrew C. (Journal of International Business Studies, 1991)
The growing interest in international business has been accompanied by a dramatic rise in the volume of international business research. This note examines the international business publication records for both authors and academic institutions for the ten-year period 1980-1989. Nine separate publications were reviewed containing some 659 international business articles. Weighted and unweighted rankings are reported.